ADDRESSING ACCOUNTABILITY AND TRANSPARENCY CHALLENGES IN WAQF MANAGEMENT USING BLOCKCHAIN TECHNOLOGY - Norlaila Mazura Hj. Mohaiyadin; Aini Aman; Mohd Rizal Palil; Suzana Muhamad Said (Bank Indonesia, 2022)
This study identifies how blockchain technology can address accountability and transparency challenges in waqf management system by using institutional theory and Islamic institutional logic. An interpretative qualitative research approach is employed, with case studies of Malaysian public university waqf administrators, and data analysis is performed using open, axial, and selective coding. The findings suggest that in terms of coercive isomorphism there are two transparency challenges related to blockchain solutions in the waqf management system: 1) errors in the issuance of receipts (process), which are expected to be overcome by blockchain solutions in the form of individual network technology and ID identifiers; and 2) difficulties in waqf distribution (process), which are predicted to be solved by blockchain solutions in the form of controlling tools, public ledgers, and obtaining waqf distribution data. In normative isomorphism, there are two accountability challenges with blockchain solutions in the waqf management system: 1) difficulties in controlling waqf activities (process), which are expected to be overcome by blockchain solutions which allow internal control; and 2) decisions on waqf distribution (output), which should be solved by blockchain solutions which allow awareness among stakeholders of waqf distribution. In mimetic isomorphism, there is one accountability challenge in the process which has blockchain solutions in the waqf management system, namely system integration, which is predicted to be overcome by a blockchain solution related to traceability. The contributions of the study include extending institutional theory and Islamic institutional logic, and providing blockchain best practices for waqf institutions in addressing accountability and transparency challenges.